MUATAN PENDIDIKAN KARAKTER DALAM CERITA PENDEK DI BUKU PELAJARAN BAHASA INDONESIA SMA - Main Sufanti; Anis Oktaviani; Jeni Nur Cahyati; Khabib Sholeh (Universitas Sebelas Maret, 2020)
This study aims to (1) Describe short stories published in Indonesian textbooks for high school. (2) Describe the content of character education in short stories in Indonesian textbooks for high school. This research is a qualitative descriptive study. Data in this study are words, sentences and paragraphs in short stories in Indonesian textbooks for high school. Data sources in this study are Indonesian language textbooks for high schools which are still used in high school, both based on the 2006 curriculum and based on the 2013 curriculum. Data collection techniques used in this study are intensive reading and recording techniques. Data analysis techniques with heuristic and hermeunitic techniques. The results of this study are as follows. (1) The study found 18 lessons in Indonesian language studies, 3 books that did not include a pen, and 15 books included a pen. In 15 lessons found 27 short stories. (2) Short stories in sufficient learning have the potential for 12 educational values of religious character, responsibility, social scrutiny, love, honesty, hard work, tolerance, nationalism, water love, friendship, democracy, and curiosity. The most frequently occurring educational values of character are religious, responsibility, social scrutiny, and love.